2019
DOI: 10.1108/jd-11-2018-0186
|View full text |Cite
|
Sign up to set email alerts
|

The role of serendipity in the story ideation process of print media journalists

Abstract: Purpose The purpose of this paper is to build upon the studies of journalism from an LIS perspective by exploring and differentiating the purposive behavior of newspaper reporters from their serendipitous encounters with information that lead to new story ideas. This paper also provides a path toward pedagogical improvements in training the modern journalism workforce in being more open to creative story ideas. Design/methodology/approach This study utilized semi-structured telephone interviews. Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 39 publications
(53 reference statements)
1
13
0
Order By: Relevance
“…Our research reveals that consumers induce less purchase intention of unexpected products when they experience serendipity than when they experience personal choice. The extant literature on serendipity showed that serendipity in an encounter can bri many benefits from different fields and perspectives, such as the exploration of business opportunities on the platform for technology companies ( Moretto and Vasilchenko, 2011 ), the source of creative story ideas for media reporters ( Bird-Meyer et al, 2019 ), the possibility of information seeking behaviors for lawyers ( Solomon and Bronstein, 2016 ). However, these studies mainly focus on the positive effect of serendipity.…”
Section: Discussionmentioning
confidence: 99%
“…Our research reveals that consumers induce less purchase intention of unexpected products when they experience serendipity than when they experience personal choice. The extant literature on serendipity showed that serendipity in an encounter can bri many benefits from different fields and perspectives, such as the exploration of business opportunities on the platform for technology companies ( Moretto and Vasilchenko, 2011 ), the source of creative story ideas for media reporters ( Bird-Meyer et al, 2019 ), the possibility of information seeking behaviors for lawyers ( Solomon and Bronstein, 2016 ). However, these studies mainly focus on the positive effect of serendipity.…”
Section: Discussionmentioning
confidence: 99%
“…Nicholas and Martin’s description of stimulus is similar to the concept of serendipity in information behaviors. Bird-Meyer et al (2019) found serendipity plays a role in journalists’ story ideation process. Journalists have an educational background, experience, and knowledge that gives them a “highly developed news sense,” or an ability to identify when a story is newsworthy (Bird-Meyer et al, 2019:1009).…”
Section: Literature Reviewmentioning
confidence: 94%
“…Bird-Meyer et al (2019) found serendipity plays a role in journalists’ story ideation process. Journalists have an educational background, experience, and knowledge that gives them a “highly developed news sense,” or an ability to identify when a story is newsworthy (Bird-Meyer et al, 2019:1009). In addition, beat reporters or specialized reporters (journalists who focus on covering a particular subject, industry, or institution) have specialized knowledge that contributes to their news sense for stories in their subject area.…”
Section: Literature Reviewmentioning
confidence: 94%
See 1 more Smart Citation
“…Serendipity can help organizations be more creative and innovative (Cunha, 2010). Past studies on IE have looked at serendipity conceptually (Erdelez, 2005;Agarwal, 2015), in various information environmentsphysical (Björneborn, 2008) and digital (McCay-Peet & Toms, 2017), learning (Giordano, 2010), different user groups such as historians (Buchanan & Erdelez, 2019), journalists (Bird-Meyer, Erdelez, & Bossaller, 2019), shoppers (Ocepek, 2017), and various other contexts of information behavior (Agarwal, 2018), but were not focused on how people experience IE in an organizational context. Ocepek (2018) argues that everyday includes work.…”
Section: Background and Literature Reviewmentioning
confidence: 99%